Development of running shoe selection using case based reasoning / Nurhafiza Suhaimi - Suhaimi, Nurhafiza (2009)
Selecting a suitable running shoe is important for runners in order to improve their performance as well as to prevent injuries. However, runners faced difficulties when it comes to selecting a suitable running shoe for them because there are many criteria to be considered in selecting running shoe. Case based reasoning can be used to adapt and combine old solutions to solve new problems, where in problem solving, the goal of case based reasoning is to build a solution to a new case based on the adaptation of solutions to past cases. It can propose solutions from incomplete problem statement make it the process of solving the problems become easier and faster. The old solutions that were the running shoe for certain criteria can be used in order to solve new problems where some criteria have been added. The objective of this research gained from the understanding of the problem statement. This research intends to provide a suitable running shoe based on the criterion chosen. In this research, cases are constructed based on the empirical data analysis performed by studying about the running shoe, criterion that is important in selecting a running shoe. The result of the criterion selected by using case based reasoning is clear and easier for runners to choose their running shoe. Finally, a prototype with interactive graphical user interface (GUI) was developed.